Blazing a trail when the road ends Shin Yong-ho, entrepreneur and creator of the world's first education insurance - In-yeong,Jeong; Carruth, David (Irvine, California Seoul Selection, 2018)
"This book tells the life story of Shin Yong-ho, who founded and built Kyobo Life Insurance, Kyobo Book Centre, and the Daesan Foundation. Shin contracted a terrible illness in his childhood, and by the time he had recovered, it was too late to go to school. Despite missing his chance to receive a formal education, he taught himself through a thousand-day reading project and through hands-on learning. After heading to Seoul by himself at the age of twenty, he moved to China and built a company from scratch. Meanwhile, a meeting with the patriotic poet Yi Yuk-sa inspired him to support the independence movement and pursue his ambition of becoming a capitalist for the Korean people. At the end of World War II, Shin returned to Korea penniless, but he kept his spirits strong and with a great deal of effort invented the concept of education insurance to satisfy Koreans' thirst for learning. His decision to establish Kyobo Book Centre under the slogan "People make books, and books make people" in the middle of Gwanghwamun in downtown Seoul illustrates his passion for promoting national education and the way he put that into practice. Shin was unstinting in his support of public interest projects, and he established the Daesan Foundation to contribute to the development and globalization of Korean literature, along with the Daesan Agricultural Foundation (originally the Daesan Foundation for Rural Culture and Society) and the Kyobo Foundation for Education. It was Shin, with his profound knowledge of literature, who suggested putting up a billboard at Gwanghwamun (this became known as the Gwanghwamun Geulpan) to carry messages of comfort and hope for the busy pedestrians crossing that intersection. All this sprang from the insight that Shin gained by carefully examining each situation from all possible angles. Shin was a great entrepreneur who did not content himself with business success and never stopped striving for the development of his country and the future of his people. He was given the John S. Bickley Founder's Award, which is regarded as the Nobel Prize in the field of insurance; he was named the Insurance Mentor; and he became the first businessperson to be awarded the Geumgwan (Golden Crown) Order of Cultural Merit. The endless creativity and ambition evident in Shin's life teach us the wisdom and courage that we need in our own."
"The original Korean-language edition was published by Kyobo Book Centre Co., Ltd."--Title page verso
Keywords: Shin Yong-Ho -- 1917-2003.; Businesspeople -- Korea (South) -- Biography; Life insurance -- Korea (South)